How Blockchain and IoT-Based Decentralized System Solves ULD Rental Problem of Airlines - Lim, Janghyuk (Archives of Business Research, 2021)
This study is devoted to ULD (Unit Load Device) rental among airlines and air cargo terminals at airports through data exchange. When airlines want to rent their partner airline’s ULD, they use it after receiving data through its ULD inventory management system. This paper proposes a de-centralized ULD rental solution by combining blockchain technology and IoT (Internet of Things). The airline that wants to rent a partner airline’s ULD checks the available inventory information before use and pays the amount according to the time of service. In addition, the smart contract specifies the remittance status to activate IoT on the ULD. Airlines that supply ULDs for partner airlines first create inventory information to provide services. Airlines that want to rent ULDs can check availability and remit rental costs according to usage time in cryptocurrency. The ULD rental service ends when the usage time is over. This ULD rental solution allows all airlines rent out their ULDs to partner airlines in real-time. Also, when a specific airport runs out of its own ULD, it is possible to overcome the difficulties of inventory shortage by renting the inventory of partner air-lines.